STRUCTURAL DESIGN OF KAWASAN KOMPLEKS ATLET IN NEW CAPITAL CITY - Limoris, Justin
The final project contains the design process of a reinforced concrete beam structure system and flat slab of Athletes Complex Area in new capital city. The structure consists of roof and main building with an elevation of +27,6 meters consisting of 2 basement floor, 4 floor and curved steel roof. The structure has basement with depth of 8,8 meters (ground floor elevation +0,8 meters). The seismic force resisting system used to design this building is Special Moment Frame (SMF) for the upper structure and elastic design for lower structure. The main structure is designed using ETABS and roof is designed using SAP2000. Structure design are based on SNI 1727 – 2013 for working load in the building, SNI 1726 – 2019 for designing seismic resistant building, SNI 2847 – 2019 for designing reinforced concrete structure, and SNI 1729 – 2015 for designing steel structure. Other programs that used is pcaColumn for column detailing. Other detailing are done manually based on internal forces that obtained from ETABS and SAP2000.